Papa's dream [compact disc] - Guerrero, Lalo (Music for Little People, 1995)
Los Lobos and Lalo Guerrero join together to bring children this collection of classic rock 'n' roll favorites and traditional Mexican Folk songs. It includes La Bamba, Wooly Bully, Cielito Lindo and more.